A survey of modern algebra - Birkhoff Garrett and Lune Saunderrs Mac (Universities press, Hyderabad, 2003)
Stats/Maths
UGC X PLAN (2004-2005)
ENGLISH
Keywords: A survey of modern algebra; Stats/Maths; Stats/Maths